Pengaruh Model Pembelajaran Discovery Learning terhadap Pemahaman Konsep Materi Wujud Zat dan Perubahannya Kelas IV Sekolah Dasar - Ida Bayu Khori’ana; Iqnatia Alfiansyah; Nataria Wahyuning Subayani (Politeknik Kampar, 2025)
This study aims to prove whether or not there is an influence of the discovery learning model on the understanding of the concept of substance form material and its changes in grade IV elementary school. The method used in this study is an experimental method with a quasi experimental type. The design in this study, namely none-equivalent control group design, this study involves two classes, namely the experimental class, namely class IV A, which is treated with learning using the discovery learning model, while the control class, namely IV B, is taught without using the discovery learning model.